Re-thinking the Power of Indigeneous Knowledge for Advancing Innovation in the Development of Rural Communities in Africa - Kamba, Manir Abdullahi (MiddleBelt Journal of Library and Information Science, 2016)
This paper highlighted the potentials of indigenous knowledge in advancing innovation and development in rural communities in Africa. It further made a critical excursion into the different types of indigenous knowledge existing in African rural communities, which could serve as an innovative system and a source for rural community development in Africa. The paper also presented both the reasons and limitations why rural communities in Africa are not developing as a consequence of ignoring their indigenous knowledge and subscribed to the western model of innovation and development. The paper also proposed a conceptual model through which rural communities can rethink and revisit the potentials of indigenous knowledge for their development rather than relying on the western innovation and development.